2008
DOI: 10.1037/1076-898x.14.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting the once-seen face: Estimating the strength of an eyewitness's memory representation.

Abstract: The fidelity of an eyewitness's memory representation is an issue of paramount forensic concern. Psychological science has been unable to offer more than vague generalities concerning the relation of retention interval to memory trace strength for the once-seen face. A meta-analysis of 53 facial memory studies produced a highly reliable association (r=.18, d=0.37) between longer retention intervals and positive forgetting of once-seen faces, an effect equally strong for both face recognition and eyewitness ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 69 publications
1
100
0
1
Order By: Relevance
“…However, there is normally a negative relationship between delay and face recognition (Deffenbacher, Bornstein, McGorty, & Penrod, 2008), and similar effects were predicted in Experiment 2.…”
mentioning
confidence: 68%
“…However, there is normally a negative relationship between delay and face recognition (Deffenbacher, Bornstein, McGorty, & Penrod, 2008), and similar effects were predicted in Experiment 2.…”
mentioning
confidence: 68%
“…For example, witnessing crimes under poor lighting conditions (G. Loftus, 2010), for a short amount of time (Bornstein, Deffenbacher, Penrod, & McGorty, 2012), from great distances (Lampinen, Erickson, Moore, & Hittson, 2014), or committed by someone of a different race (Meissner & Brigham, 2001) can greatly reduce identification accuracy. Long delays (or retention intervals) between the crime event and memory test may also weaken eyewitness memory (Deffenbacher, Bornstein, McGorty, & Penrod, 2008;Wheatcroft, Wagstaff, & Manarin, 2015) and, further, increase the risk of exposure to post-event information and suggestion (e.g., media reports and conversations with other witnesses), which may distort witnesses' recollections of their experiences (E. Loftus, 2005).…”
Section: Eyewitness Memory and Juror Evaluations Of Witness Evidencementioning
confidence: 99%
“…Dysart and Lindsay (2007b) concluded that delay adversely influences showups after 24 hours, and probably increases errors in both culprit-present and culprit-absent lineups, although other factors may have more impact. In a meta-analysis of 57 studies, Deffenbacher, Bornstein, McGorty and Penrod (2008) found a reliable association between longer retention intervals and lower identification accuracy of faces seen once. The effect was equally strong in face recognition paradigms (which usually required discrimination of many faces previously seen once from new faces), and in eyewitness identification paradigms, which usually require identification of a single person from a lineup.…”
Section: Methodsmentioning
confidence: 99%